NODAL in the Uterus Is Necessary for Proper Placental Development and Maintenance of Pregnancy - Park, Craig B. (Biol Reprod, 2012)
Preterm birth is the single leading cause of perinatal mortality in developed countries, affecting approximately 12% of pregnancies and accounting for 75% of neonatal loss in the United States. Despite the prevalence and severity of premature delivery, the causes and mechanisms that underlie spontaneous and idiopathic preterm birth remain unknown. Our inability to elucidate these fundamental causes has been attributed to a poor understanding of the signaling pathways associated with the premature induction of parturition and a lack of suitable animal models available for preterm birth research. In this study, we describe the generation and analysis of a novel conditional knockout of the transforming growth factor beta (TGFB) superfamily member, Nodal, from the maternal reproductive tract of mice. Strikingly, uterine Nodal knockout females exhibited a severe malformation of the maternal decidua basalis during placentation, leading to significant intrauterine growth restriction, and ultimately preterm birth and fetal loss on Day 17.5 of gestation. Using several approaches, we characterized aberrant placental development and demonstrated that reduced proliferation combined with increased apoptosis resulted in a diminished decidua basalis and compromised maternal-fetal interface. Last, we evaluated various components of the established parturition cascade and determined that preterm birth derived from the maternal Nodal knockout occurs prior to PTGS2 (COX-2) upregulation at the placental interface. Taken together, the results presented in this study highlight an in vivo role for maternal NODAL during placentation, present an interesting link between disrupted decidua basalis formation and premature parturition, and describe a potentially valuable model toward elucidating the complex processes that underlie preterm birth.